EFFECT OF PROFITABILITY, COMPANY AGE, COMPANY SIZE ON AUDIT REPORT LAG - Putri, Nurul Alifah; Rochyatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The time between the end of financial statement preparation and the date the audit report is issued is known as the audit report Iag. A long audit report Iag typically happens when a corporation misses the deadline for delivering its audited financial statements to the capital market. Due to the company's delayed release of financial results, market participants, like investors, frequently need a better impression of it. Six manufacturing companies listed on the Indonesia Stock Exchange (IDX) are the subject of this study's sample. The research methodology used is an experimental study with independent factors such as Profitability, firm age, and company size. According to the research's findings, Profitability has a favourable impact on the audit report lag. However, firm age and size have little bearing on this issue.